NEED ANALYSIS OF INSTRUCTIONAL MEDIA WITH ESQ NUANCE AS SUPLEMENT IN SENIOR HIGH SCHOOL - Khalif Alfajri; Ardi Ardi; Ganda Hijrah Selaras; Irdawati Irdawati; Heffi Alberida; Sasmeri Sasmeri (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The 2013 curriculum encourages students to be more active and independent when getting information about learning materials. Therefore, teachers are required to be able to increase students' learning motivation, one of which is by developing learning media that can attract students' learning interest. The purpose of this study was to see the needs of students for learning media with ESQ nuances about bacteria as a supplement to biology teaching materials for class X science SMAN 2 Payakumbuh. This type of research is descriptive quantitative research. The method used to collect data was done through distributing questionnaires to class XII students and interviewing two teachers, namely a biology teacher and an Islamic religious education teacher. In addition, the daily test results obtained by students were also used as data in this study. The results of the study revealed that students had difficulty in understanding biology learning about bacterial material due to the difficulty of observing micro learning objects plus less supportive learning media where the images on the learning media were of very low quality and colorless. This results in a lack of student motivation in participating in the learning process. For that we need a learning media that is easy to understand and has high quality images so that it can be studied independently by students.